2012 IEEE International Conference on Bioinformatics and Biomedicine Workshops 2012
DOI: 10.1109/bibmw.2012.6470224
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human genome annotation complexity on RNA-Seq gene expression quantification

Abstract: Next-generation sequencing (NGS) has brought human genomic research to an unprecedented era. RNA-Seq is a branch of NGS that can be used to quantify gene expression and depends on accurate annotation of the human genome (i.e., the definition of genes and all of their variants or isoforms). Multiple annotations of the human genome exist with varying complexity. However, it is not clear how the choice of genome annotation influences RNA-Seq gene expression quantification. We assess the effect of different genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…For thrombin study samples (SRA: SRP008482), we use OSA alignment with htseq-count quantification to prepare input read count data for the edgeR package. Most of the top 20 differentially expressed genes are detected in at least two of the six annotations, while several others are unique and annotation-specific [ 16 ]. Even though the functions of these annotation-specific genes are unclear, more complex annotations are still preferable since they provide an opportunity to identify novel genomic elements that may be functionally important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For thrombin study samples (SRA: SRP008482), we use OSA alignment with htseq-count quantification to prepare input read count data for the edgeR package. Most of the top 20 differentially expressed genes are detected in at least two of the six annotations, while several others are unique and annotation-specific [ 16 ]. Even though the functions of these annotation-specific genes are unclear, more complex annotations are still preferable since they provide an opportunity to identify novel genomic elements that may be functionally important.…”
Section: Resultsmentioning
confidence: 99%
“…The information sources and annotating strategies of each human genome annotation are summarized in [ 16 ]. The procedures for improving cross-annotation comparability are briefly described below:…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the approximate number of genes with detectable expression in porcine peripheral blood is still unknown. The lack of a detailed catalog and annotation of the pig genome and transcriptome hinders annotation-based high throughput studies [ 24 , 25 ]. Fortunately, two independent assemblies of the pig genome have been recently initiated using a PacBio long read-based approach [ 22 , 26 ] and are currently being annotated.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that the increasing complexity of gene annotation adversely affected DE analysis. Wu et al[23] evaluated the impact of human gene annotation choice on RNA-seq expression estimates. They defined the complexities of gene annotations in terms of the relative rank of the number of genes, isoforms, and exons and demonstrated that more complex annotation results in a smaller correlation between RNA-seq fold-change and qRT-PCR fold-change.…”
mentioning
confidence: 99%